2019
DOI: 10.1016/j.fertnstert.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-enhancing male reproductive surgery: glimpses into the past and thoughts for the future

Abstract: Over the past few decades, there have been numerous paradigm shifts in male reproductive surgery, resulting from a combination of technologic advancements in both the operating room and the laboratory. The operating microscope transformed the field of male reproductive surgery, enabling novel techniques and higher precision for the treatment of male-factor subfertility. The subsequent widespread adoption of microsurgical approaches was largely responsible for the emergence of a cadre of highly specialized male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…While VV and VE have been performed for over 100 years, data concerning practice patterns and outcomes remain sparse, as most studies originate from single‐centre, high‐volume experiences or from questionnaire‐based data (Halpern et al., 2019). In the current study, we explored the practice patterns of VV and VE in a large, geographically diverse and national commercial dataset.…”
Section: Discussionmentioning
confidence: 99%
“…While VV and VE have been performed for over 100 years, data concerning practice patterns and outcomes remain sparse, as most studies originate from single‐centre, high‐volume experiences or from questionnaire‐based data (Halpern et al., 2019). In the current study, we explored the practice patterns of VV and VE in a large, geographically diverse and national commercial dataset.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Study design; (4) Sperm extraction method; (5) Age of participants; (6) Outcome data (fertilization rates, CPRs, and take home baby rates. Nonrandomized studies were also assessed for the risk of bias [10] as shown in Supplemental Table 1.…”
Section: Data Extractionmentioning
confidence: 99%
“…Testicular sperm extraction (TESE), microscopic TESE (microTESE), or testicular sperm aspiration (TESA) are methods commonly utilized to harvest testicular sperm. When the non-obstructive azoospermia leading to infertility occurs, and sperm donor assistance is refused, testicular retrieved sperm are conventionally used [6]. During the course of an ART cycle, the source of sperms could possibly influence SDF levels [7].…”
Section: Introductionmentioning
confidence: 99%
“…The last article, by Fantus and Halpern, is entitled ''Vasovasostomy and Vasoepididymostomy: Indications, Operative Technique, and Outcomes.'' Many advances in microsurgical vasectomy reversal have occurred in recent years, and it is important for specialists in both male and female reproduction to have a clear understanding of the progress made in surgical techniques and outcomes to guide patients as they consider reproductive options after vasectomy (5). The authors detail preoperative patient assessment, state-of-the-art operative techniques for vasovasostomy and vasoepididymostomy, postoperative care, potential surgical complications, and surgical outcomes.…”
mentioning
confidence: 99%